Sosialisasi Pembukuan Digital Syariah pada Kelompok Usaha Bersama (Pengolah Krupuk, Telur Asin dan Amplang) di Desa Batakan: Socialization of Sharia Digital Bookkeeping for Joint Business Groups (Processing Crackers, Salted Eggs, and Amplang) in Batakan Village - Erziaty, Rozzana; Budi, Iman Setia; Fitriana, Yunisa; Komarudin, Parman; Arminarahmah, Nur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The Community Engagement Activity in Batakan Village is focused on the socialization of Sharia digital accounting within the Collective Business Group, attended by 49 participants. The Method of Discussion Approach with a participatory Focused Group Discussion is employed to facilitate the exchange of ideas and perspectives. Participants demonstrate high enthusiasm with a total attendance rate of 100% and active participation, including asking questions throughout the event. Socialization emphasizes using information technology and digitalizing financial accounting by introducing the Finansialku application (Finansialku.com). Evaluation indicates a significant improvement in participants' understanding after the socialization, with the category of 'good' reaching 51.02% and 'sufficient' at 36.73%. The Community Engagement Activity is highly regarded by participants in terms of speakers (87.76% good) and materials (81.63% good) based on the evaluation results. The importance of this activity is evidenced through statistical testing, with a significant value of 0.000 < p (0.05), indicating a significant difference in the participants' cognitive assessment after the socialization. Thus, the delivery of socialization material has proven effective in educating participants about Sharia digital accounting within the collective business group in Batakan Village.